2019
DOI: 10.1016/j.surfcoat.2018.12.117
|View full text |Cite
|
Sign up to set email alerts
|

High frequency pulse anodising of aluminium: Anodising kinetics and optical appearance

Abstract: High frequency pulsed anodising of pure aluminium was investigated with an aim to understand the effect of the anodising parameters on the growth kinetics of the anodic layer and optical appearance of the anodised surface. Anodising was performed in sulphuric acid, and the effect of the pulse duty cycle, applied potential offset, and pulse frequency was investigated. Optical properties of the anodised surfaces are improved upon lowering the anodising potential and by increasing the frequency of the applied pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…al. [27] showed that pulsing from zero to 15 V at 1 kHz, results in very dramatic current peak of approximately 30 A/dm 2 . As soon as the barrier layer is fully charged (during one pulse cycle), the current drops to approximately 4 A/dm 2 ; i.e.…”
Section: Figurementioning
confidence: 99%
“…al. [27] showed that pulsing from zero to 15 V at 1 kHz, results in very dramatic current peak of approximately 30 A/dm 2 . As soon as the barrier layer is fully charged (during one pulse cycle), the current drops to approximately 4 A/dm 2 ; i.e.…”
Section: Figurementioning
confidence: 99%
“…When applying a low current density, the dissolution of the Al 2 O 3 predominates over the formation of this layer. The influence of the current density value, duty factor, and pulse frequency on the forming anode layer of Al 2 O 3 has been presented, among other studies, in research [9][10][11]. The study of the pore composition and structure as well as the mechanical properties of anodic alumina layers obtained by the impulse method are presented in [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The cell size has a linear relationship with voltage, as the voltage is increasing the cell size gets bigger too and the number of pores is decreasing, respectively. The layer of Al₂O₃ forms, and chemically bonds perfectly to the metal base also the thickness of the film is increasing as the treatment operates for a longer time (16,118,119,(124)(125)(126). system (1,121) which can be linked according to the previously reported orientation relationship (16).…”
Section: Anodising Processmentioning
confidence: 88%
“…Each specific grain illustrated identical position of maximum intensity with respect to the analyser rotations. Also, the data showed each specific grain to maintain identical value for the difference between maximum and minimum intensity unconventionally to the anodised layer(16,(124)(125)(126).…”
mentioning
confidence: 85%